2014
DOI: 10.4103/0970-0358.138956
|View full text |Cite
|
Sign up to set email alerts
|

Role of the urethral plate characters in the success of tubularized incised plate urethroplasty

Abstract: Background:Today, tubularized incised plate (TIP) urethroplasty is the most commonly performed operation for distal and mid-penile hypospadias. Reports from different centers worldwide confirm its nearly universal applicability and low complications rate.Aim:Evaluation of the urethral plate characters and its effect on the outcome of TIP urethroplasty.Materials and Methods:Between 2010 and 2013, 100 children with primary distal penile hypospadias underwent TIP urethroplasty. Urethral plates were categorized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
8
0
5
Order By: Relevance
“…Further studies by Sarhan et al, K.E. Chukwubuike et al, and Aboutaleb H confirmed this finding [22, 23]. In a study by Seleim significant connection between urethral plate width and complications was found with a cutoff value of less than 4 mm [24].…”
Section: Discussionmentioning
confidence: 89%
“…Further studies by Sarhan et al, K.E. Chukwubuike et al, and Aboutaleb H confirmed this finding [22, 23]. In a study by Seleim significant connection between urethral plate width and complications was found with a cutoff value of less than 4 mm [24].…”
Section: Discussionmentioning
confidence: 89%
“…Определяющее значение, по нашему мнению, имеет состояние уретральной площадки. Многие факторы, в частности, дефицит пластического материала, анатомические особенности строения, рубцовый процесс в области ранее перенесенной операции, приводят к уменьшению размеров уретральной площадки [1,[3][4][5][6][7]. По нашим наблюдениям, исходно маленькие анатомические размеры головки полового члена, отсутствие выраженной ладьевидной ямки встречаются у 25 % первичных больных.…”
Section: Discussionunclassified
“…Плоская головка полового члена малых размеров затрудняет создание широкого участка уретры в области головки и становится, вероятно, одной из основных причин возникновения мочевых свищей в области венечной борозды [6][7][8][9][10][11]. Попытки ушивания свища в области венечной борозды без реконструкции головки часто сопровождаются рецидивом свища.…”
Section: Discussionunclassified
See 2 more Smart Citations